Safety and efficacy of the vibrating capsule, an innovative non‐pharmacological treatment modality for chronic constipation. Issue 1 (6th December 2014) - Ron, Y.; Halpern, Z.; Safadi, R.; Dickman, R.; Dekel, R.; Sperber, A. D.
Abstract Background Constipation is a common disorder. Because the prevalence is high and the satisfaction level with currently available treatment is low, there is an unmet need for innovative treatment. We assessed the safety and efficacy of the Vibrant Capsule, a non‐pharmacological device that is assumed to induce a normal peristaltic wave in the large intestine to alleviate constipation. Methods Two animal safety studies and a safety study on healthy volunteers were conducted, followed by a prospective, non‐randomized, open‐label, single group assignment, safety and efficacy study. The latter was conducted among 26 patients who ingested the capsule twice weekly for a study period of 7.5 weeks, after a run‐in period of 2 weeks without usual treatment for constipation. Key Results In the studies on animals and healthy volunteers, there were no adverse events. Twenty‐eight patients began the clinical trial and 26 completed it (25 women). The mean age was 47.0 ± 12.6 years (range: 19–65). The two dropouts, who completed the safety phase, and the 26 who completed the entire study expelled the capsule without difficulty. Twelve participants reported 27 adverse events, none serious, and all transient. There was a significant increase of 1.60 ± 1.09 in the mean number of bowel movements/week from 2.19 ± 0.67 to 3.79 ± 1.31 (p < 0.001). This increase was seen in 23 of the 26 patients (88.5%). The mean number of spontaneous bowel movements for the study group increased in each treatment week compared to baseline. Conclusions & Inferences The Vibrant Capsule is safe and potentially effective in the treatment of constipation, justifying randomized controlled studies.